Impact of non-steroidal anti-inflammatory drugs on malignant transformation in oral lichen planus: insights from a real-world cohort study - Seebauer, Christian; Ludwig, Ralf; Sieg, Peter; Olbrich, Henning; Curman, Philip (Frontiers in Pharmacology, 2026)
IntroductionOral lichen planus (OLP) is a chronic inflammatory condition with malignant potential for oral squamous cell carcinoma (OSCC). Differential risks of pharmacological treatments, particularly long-term use, remain unclear. We aimed to quantify OSCC risk across treatment modalities and assess potential benefit of combining immunosuppressive and anti-inflammatory agents to inform safer strategies.MethodsWe conducted a large, retrospective cohort study with propensity score matching to balance demographic and clinical covariates. Patients with OLP treated with either systemic or topical glucocorticoids, calcineurin inhibitors, non-steroidal anti-inflammatory drugs (NSAIDs), or combinations were followed. OSCC incidence rates were compared between treatment groups, controlling for confounders and stratifying by route and duration of therapy.ResultsCompared with glucocorticoid regimens, calcineurin inhibitors were associated with higher OSCC risk (glucocorticoids: HR 1.85, 95% CI 1.48–2.32; calcineurin inhibitors: HR 3.17, 1.48–6.76). The lowest risk was seen with topical glucocorticoids. Concomitant NSAIDs, particularly ketorolac and diclofenac, with topical glucocorticoids or calcineurin inhibitors, reduced OSCC risk (topical glucocorticoids: HR 0.73, 0.58–0.91; plus ketorolac: HR 0.63, 0.38–1.04; topical calcineurin inhibitors alone: HR 1.53, 1.03–2.28; plus ketorolac: HR 0.28, 0.15–0.54). Owing to retrospective design and reliance on ICD-10 coding, residual confounding and misclassification cannot be excluded.ConclusionCalcineurin inhibitors carry high risk for malignant transformation in OLP, while topical glucocorticoids, especially NSAID/glucocorticoid combinations, offer safer profiles. These findings call for re-evaluation of treatment guidelines and prospective trials assessing novel or combination therapeutics that optimize long-term safety and symptom control in OLP.